The use of a multi-disciplinary geriatric telemedicine service (TELEG) and its acceptance at a tertiary care centre in Malaysia - Ting, Chuo Yew; Nur Hidayati, Abdul Halim; Ling, Jia Nee; Tiong, Ing Khieng; Nor Izzah, H J Ahmad Shauki; Lee, Yew Fong *; Nor Anizah, Osman; Chai, Gin Wei; Ung, Shin Han; Ang, Melinda (BMC, 2024)
Background: The COVID-19 pandemic has fueled the widespread adoption of telemedicine in healthcare, particularly in Sarawak, Malaysia. This study investigates the use and acceptance of Sarawak's inaugural multidisciplinary geriatric telemedicine service, TELEG.